PENGEMBANGAN MI BASAH DENGAN PENAMBAHAN IKAN MUJAIR SEBAGAI PANGAN ALTERNATIF UNTUK BALITA: DEVELOPMENT OF WET NOODLES WITH ADDITIONAL MUJAIR FISH AS AN ALTERNATIVE FOOD FOR TODDLERS - Mannan, Muthia Muthmainnah; Reisi Nurdiani (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2025)
Introduction: Stunting in toddlers due to malnutrition is still a major problem in Indonesia. Instant noodles as a practical food are often consumed by children, but have limited nutritional content. Modification of instant noodles with the addition of tilapia fish has the potential to improve nutritional quality. Aim: This study aims to develop wet noodles made from wheat flour with the addition of tilapia fish which is expected to be an alternative nutritious food. This study analyzed the organoleptic value and nutritional content of wet noodles. Materials and Method: This experimental study was conducted with a single factor in the form of the addition of tilapia fish from December 2023 to January 2024. The formula consisted of F1 (10% fish), F2 (15% fish), and F3 (20% fish). Data were obtained through hedonic tests, hedonic quality, and nutrient analysis (air, ash, protein, fat, carbohydrates) using one-way ANOVA statistical tests and Duncan's test. Results: The wet noodle formula with the addition of 15% tilapia fish(F2) was the most preferred product, although the aroma and distinctive taste of fish were significant (p <0.05). The protein content in F2 of 4.97% meets the standard requirements for MPASI for children aged 12-24 months according to BPOM standard Number 24 of 2020, and the total fat content is <4.5 g/100 kcal. Conclusion: Tilapia wet noodles have the potential to be a nutritious and preferred alternative MPASI and support adequate nutrition for toddlers.Keywords: Stunting, MPASI, Organoleptic Test, Nutrient Analysis